Case report: A rare case of acute myeloid leukemia with CPSF6–RARG fusion resembling acute promyelocytic leukemia - Zhao, Junmei; Wang, Wentao; Yan, Li; Chen, Xi; Li, Wen; Li, Wanying; Chen, Tingting; Chen, Lunhua (Frontiers in Oncology, 2022)
Retinoic acid receptor gamma (RARG) gene rearrangement has been reported in several acute myeloid leukemia (AML) patients. They resemble classical acute promyelocytic leukemia (APL) patients in clinical features, morphology and immunophenotype, but don’t carry promyelocytic leukemia (PML)–RARA fusion gene. Importantly, almost all these APL-like AML patients show resistance to all-trans retinoic acid (ATRA), and no effective treatment is recommended for them. Here, we identified a case of AML resembling APL in clinical presentation and experimental findings carrying a rare cleavage and polyadenylation specific factor 6 (CPSF6)-RARG fusion gene. The patient was insensitive to ATRA and ATO, but responded well to homoharringtonine and cytarabine.